Institute of Metals Division - Observations on Cleavage and Polygonization of Molybdenum Single Crystals - Neng-Kuan Chen; Robert Maddin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
THE (001) planes have been reported as the cleavage planes in body-centered cubic metals such as alpha-iron and tungsten.' However, in molybdenum, which is also body-centered cubic, experimental X-ray evidence indicating a similar cleavage plane still seems lacking. Tsien and Chow" observed microscopically in the extension at around 1000°C of molybdenum single crystalline wires 0.25 mm in diam that the fracture plane seemed to be parallel to the operative slip plane, which appeared to be (110) at that temperature. Zapffe' pointed out from fractographic study of polycrystalline molybdenum that "although the transgranular pattern is characteristically non-crystallographic, patterns occasionally reveal {100} cleavage." This has been generally assumed to be the case at ordinary temperatures. In the present experiments, a single crystal of Fansteel molybdenum, Vs in. diam x 2 in. long, prepared by the methods described by Chen, Maddin, and Pond" was fractured at room temperature by bending. The fracture surface appeared to be quite similar to the cleavage surface of zinc and was crys-tallographic. A back-reflection Laue photogram was made using 35 kv copper white radiation; the X-ray